Analisis Penilaian Tingkat Kesehatan Di BMT UGT Sidogiri Cabang Glenmore Kabupaten Banyuwangi - Lely Ana Ferawati Ekaningsih; Munawir Munawir; Faiqotul Umi Hanik (Jurnal Istiqro, 2020)
This study aims to 1) To analyze the level of the financial health of BMT UGT Sidogiri Glenmore Banyuwangi Branch using the RGEC method 2) To analyze the level of the financial health of BMT UGT Sidogiri Glenmore Branch by using the State Cooperative Cooperative and Small and Medium Enterprises number 35.3 / Per / M.KUKM / X / 2007, 3) To analyze the comparison of health level measurements in BMG UGT Sidogiri Glenmore using the RGEC and Permen methods. This type of research is comparative. The secondary data type is in the form of BMT Sidogiri financial statements. The analysis tool uses a horizontal analysis. 1) The results of the BMT UGT Sidogiri health assessment from 2017 to 2018 are measured better using RGEC as a whole is quite healthy. 2) Results Sweets as a whole have a healthy predicate. 3) the results of the analysis and calculation of RGEC and Permen obtained conclusions if BMT Sidogiri is in good health